Association between head circumference growth and peripheral nerve cross-sectional area growth in infants: a potential future biomarker for central and peripheral nerve maturation - Bürke, Noé; Jansen, Lynn; West, Erin; Wurster, Janina; Broser, Philip Julian (Neuropediatrics)
Aim: To analyze the association between the growth of the central and peripheral nervous systems in children aged 0 to 3 years. Method: A total of 40 participants were included in this cross-sectional study to analyze the association between the growth development of the peripheral and central nervous system. Using high-resolution ultrasound, the cross-sectional area of the median nerve was measured at three locations (wrist, forearm, and upper arm) representing the development of the peripheral nervous system and then compared to the head circumference as proxy for the central nervous system development. Results: There was a significant correlation between head circumference and the cross-sectional area of the median nerve at the three measured locations. When looking at adjusted linear regression models, head circumference appeared to be a stronger predictor of nerve cross-sectional area size than age. Interpretation: The observed association between nerve cross-sectional areas and head circumference growth indicates a parallel size increase. This association may have clinical relevance because both head circumference and nerve cross-sectional area could potentially serve as complementary markers for neurodevelopmental monitoring, i.e. myelination and may contribute to the early identification of atypical developmental patterns, though confirmatory longitudinal data are required.